Search for Bc+ decays to the pp[bar]π+ final state - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physics letters, 2016)
A search for the decays of the Bc+ meson to pp¯π+ is performed for the first time using a data sample corresponding to an integrated luminosity of 3.0 fb−1 collected by the LHCb experiment in pp collisions at centre-of-mass energies of 7 and 8 TeV. No signal is found and an upper limit, at 95% confidence level, is set, fcfu×B(Bc+→pp‾π+)<3.6×10−8 in the kinematic region m(pp‾)<2.85 GeV/c2, pT(B)<20 GeV/c and 2.0<y(B)<4.5, where B is the branching fraction and fc (fu) is the fragmentation fraction of the b quark into a Bc+ (B+) meson.
*The LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und 704 weitere Personen]
Im Titel ist das Zeichen + hochgestellt
Im Titel ist der Buchstabe c tiefgestellt
Im Titel steht der Buchstabe p mit einem Oberstrich
Gesehen am 16.07.2020